P2RX1 promotes mitochondrial apoptosis via calcium/CaM KII-mediated suppression of PI3K/Akt signaling in Philadelphia chromosome-positive acute lymphoblastic leukemia - Li, Xiao bing; Ren, Qin; Ye, Xiang mei; Li, Jing lie; Feng, Lei guang (Frontiers in Pediatrics, 2025)
IntroductionPhiladelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL) continues to pose a major clinical challenge. Although tyrosine kinase inhibitor (TKIs)-based regimens form the cornerstone of therapy, treatment outcomes are compromised by difficulties in achieving remission, high relapse rates, and the critical issue of drug resistance. This study aims to elucidate the role of the purinergic receptor P2RX1 in the pathogenesis of and therapeutic response in Ph+ ALL.MethodsBy analyzing P2RX1 expression levels in an online patient database and its association with prognosis, we evaluated the potential significance of this receptor in clinical outcomes. A P2RX1 overexpression model was established in the SUP-B15 Ph+ ALL cell line, and a series of functional experiments were conducted to assess its impact on tyrosine kinase inhibitor-induced apoptosis and proliferation capacity. To further elucidate its mechanism of action, we monitored changes in intracellular calcium ion concentration, mitochondrial membrane potential, and ATP production levels. Additionally, RT-PCR and Western blot analysis were employed to assess the activation status of the PI3K/Akt signaling pathway, CaMKII, and apoptosis-related proteins BAX, BAD, cytochrome C, and caspasesResultsAnalysis of the online patient database revealed that high expression of P2RX1 was significantly associated with poor clinical outcomes. Functional experiments demonstrated that overexpression of P2RX1 in SUP-B15 cells markedly enhanced their sensitivity to apoptosis induced by tyrosine kinase inhibitors; conversely, treatment with the CaMKII inhibitor KN-62 significantly suppressed cell proliferation. Mechanistically, excessive P2RX1 activation disrupts intracellular calcium homeostasis, leading to reduced mitochondrial membrane potential and ATP depletion, thereby activating the intrinsic apoptotic pathway. This process involves inhibition of the PI3K/Akt signaling pathway, hyperactivation of CaMKII, and upregulation of pro-apoptotic proteins such as BAX, Bad, cytochrome C, and cleaved caspase-3 and cleaved caspase-9.ConclusionThis study reveals the role of P2RX1 as a calcium-regulated tumor suppressor in Ph+ ALL, promoting apoptosis by disrupting mitochondrial function and inhibiting the PI3K/Akt survival signaling pathway, thereby providing a novel therapeutic approach to overcome TKI resistance.